CAN MOTHERS JUST ‘SING THEIR TROUBLES AWAY’?: AN INTEGRATIVE REVIEW OF SINGING AND MATERNAL MENTAL HEALTH - Brown Vallim Brisola , Elizabeth; Ilari, Beatriz (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2021)
Although motherhood is often associated with expectations of happiness and fulfillment, for many women it actually brings anxiety and distress. As women engage in daily tasks of childcare, they commonly use music and singing to communicate with and regulate their infant’s emotions. Though not widely disseminated in the mental health field, a growing number of studies, mental health projects, and interventions have addressed the psychosocial and cultural aspects of maternal singing. Scholars have documented its effects and benefits, and revealed its value as a non-pharmacological mental health tool for both mother and infant. The present article reviews literature from the past 10 years on maternal singing to infants, with the aim of understanding and describing its impact on maternal mental health. Seventeen publications that met our pre-established criteria draw attention to the potential of maternal singing both as a palliative and preventive measure for individual mothers and for mothers in group programs, including those who are healthy or suffering from postnatal depression. These studies point to singing as a tool to deepen mother-infant bonds; as a vehicle of emotional expression; as a mnemonic channel for memories of past experiences; and as a mechanism to help mothers engage positively with daily chores and childcare, giving them a sense of achievement and increased self-esteem. Group singing studies point to mothers feeling connected with others, learning parenting "repertoire", and changing their "tempo". Several suggestions are presented to incorporate singing to already existing programs and to the daily care of infants, as well as for further research.